2011
DOI: 10.1074/jbc.m110.197681
|View full text |Cite
|
Sign up to set email alerts
|

Apoptosis-associated Speck-like Protein (ASC) Controls Legionella pneumophila Infection in Human Monocytes

Abstract: The ability of Legionella pneumophila to cause pneumonia is determined by its capability to evade the immune system and grow within human monocytes and their derived macrophages. Human monocytes efficiently activate caspase-1 in response to Salmonella but not to L. pneumophila. The molecular mechanism for the lack of inflammasome activation during L. pneumophila infection is unknown. Evaluation of the expression of several inflammasome components in human monocytes during L. pneumophila infection revealed that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
78
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
8
1
1

Relationship

2
8

Authors

Journals

citations
Cited by 58 publications
(80 citation statements)
references
References 44 publications
2
78
0
Order By: Relevance
“…Therefore, one could speculate that Naip5 A/J provides susceptibility to Legionella infection by altering the cyclin system, which in turn affects apoptosis (Xaus et al 2001). In agreement with our findings, intracellular survival of Legionella in macrophages has been previously reported to involve modulation of apoptosis (Abdelaziz et al 2010;Nogueira et al 2009). …”
Section: Discussionsupporting
confidence: 90%
“…Therefore, one could speculate that Naip5 A/J provides susceptibility to Legionella infection by altering the cyclin system, which in turn affects apoptosis (Xaus et al 2001). In agreement with our findings, intracellular survival of Legionella in macrophages has been previously reported to involve modulation of apoptosis (Abdelaziz et al 2010;Nogueira et al 2009). …”
Section: Discussionsupporting
confidence: 90%
“…In this study, we found the expression of ASC, but not NLRP3, was controlled by MAVS-TRAF3 signaling axis, because deficiency of MAVS results in almost complete depletion of ASC protein levels with unchanged NLRP3 expression. Legionella pneumophila has been shown to block the formation of inflammasome complexes by interfering with the transcription of gene-encoding ASC and preventing ASC expression (34,35). ASC is considered the key to caspase-1 activation within the inflammasome in response to almost all upstream triggers known to induce maturation of IL-1b.…”
Section: Discussionmentioning
confidence: 99%
“…The Nlrc4 inflammasome restricts Legionella growth in in vitro-cultured macrophages and in the lungs of infected mice (39,40). This pathogen interferes with the transcription upregulation of the inflammasome adaptor ASC to safeguard its proliferation in human monocytes (41). F. tularensis makes use of the putative lipid II flippase mviN to dampen activation of the AIM2 inflammasome (42).…”
Section: Modulation Of Inflammasome Activation By Bacterial Virulencementioning
confidence: 99%